The concept of freedom in decisions on freedom of conscience of the Colombian Constitutional Court (2016)
This paper is a hermeneutical analysis of the concept of freedom in order to understand in what sense the freedom of conscience, which is a positive way of the freedom in philosophical sense, is understood by the provisions of the Colombian Constitutional Court. Thus, the classic definitions of positive and negative liberty are taken into account to determine which of these two meanings is the most prevalent in the judgments of the Court and thereby to establish whether the formulation of Social State of Law set forth in the Constitution, which prioritizes the positive duties of the State, is real and effective. This analysis will be based on some paradigmatic cases in which the freedom of conscience right has been violated.